Population Structure and Genetic Diversity of Sporothrix globosa in China According to 10 Novel Microsatellite Loci. Issue 2 (13th December 2018) - Gong, Jie; Zhang, Mingrui; Wang, yu; Li, Ruoyu; He, Lihua; Wan, Zhe; Li, Fuqiu; Zhang, Jianzhong
Abstract : Purpose. Sporothrix globosa is the most important agent of sporotrichosis in China. The aim of this study is to investigate the population parameters of S. globosa . Methodology. In the present study, we developed a set of microsatellite markers that have a cumulative discriminatory power of 1.000. Using these microsatellite loci, 120 strains of S. globosa that had clear sampling information were analysed. Results. Population structure analyses revealed that S. globosa can be separated into three clusters. Analysis of molecular variance (AMOVA) results indicated that genetic variation was more significant among these three clusters than between the two clinical types analysed. In addition, cluster II might have the widest range of distribution and contain higher genetic diversity than the other clusters. Conclusions. Our work is the first to develop a suite of highly discriminatory microsatellite markers and reveal the population parameters of S. globosa, and our results suggest that different lineages can coexist in two different clinical types. In addition, it was hypothesised that lineages with higher genetic diversity might have a wider distribution range.